Enhancing the productivity of pyramid solar still utilizing repurposed finishing pads as cost-effective porous material - Suraparaju, Subbarama Kousik; Peddojula, Mohana Krishna; Mahendran, Samykano; El-Sebaey, Mahmoud S.; Kadambari, CS Vyasa Krishnaji; Budala, Swapna Babu; Manepalli, TN VV Ramkumar; Reddy, Lavanya; Vardhanapu, Sanjay Raju; Ajjada, Bhogeswara Rao; Pilli, Ramesh Babu (Taylor & Francis, 2024)
The primary objective of the current research is to augment the potable water yield of the solar still (SS). This objective is achieved by integrating a used brushed refinishing pad (BRP) as a porous material (PM) in the absorber basin. This integration maximizes the wet surface area due to the pad's porous nature, thereby enhancing photothermal absorption, which is the process where a material absorbs light and converts it into heat. An experimental investigation was conducted to analyze the effect of porous materials in a rectangular pyramid solar still (RPSS) regarding potable water yield and feasibility. The results were compared with those of the conventional solar still (CSS), revealing a noteworthy enhancement in the production of potable water with RPSS-PM, showing a 47.7 % increase on day one and a 48.1 % increase on the second day with a mere 10 % rise in basin water temperatures. The energy efficiency of RPSS-PM improved significantly by about 9 % on both days compared to CSS. From an economic perspective, this system's payback period (PBP) was 5.2 months, compared to 6.1 months for the CSS. Furthermore, the cost per liter (CPL) of potable water produced by the RPSS-PM was 16.6 % lower than that of the CSS. This innovative approach holds great potential for effectively addressing challenges related to water scarcity.